Financing of Eco-innovations: Sources and Trends in Kazakhstan - Gaukhar, Kalkabayeva; Rakhmetova, AibotÐ°; Assanova, Marina (International Journal of Energy Economics and Policy, 2020)
Nowadays most developed and some developing countries are moving to the path of "green" economy and strive to develop in the direction of sustainable development. An important aspect is the development of eco-innovations that contribute to reducing the negative impact on the environment through the creation of fundamentally new products, processes and systems with minimal use of natural resources and virtually zero environmental pollution. Such clean technologies are possible in the field of renewable energy, water resources management, "green" construction, waste reduction, etc. The vast accumulated international experience of countries that develop eco-innovations serves as a positive experience for the development of this direction in Kazakhstan. Energy efficiency and renewable energy resources should be considered as national priorities of the country, be integrated into energy and socio-economic policies, and become the basis for the development of state programs for sustainable development. Kazakhstan strives to achieve its goals for sustainable development, including improving the environmental situation in the country. This paper focuses on financial issues in eco-innovations, it represents analyses of current trends in this sphere in Kazakhstan. Keywords: eco-innovations, sustainable development, regional development, financing of ecological innovations, innovative development JEL Classification: O310 DOI: https://doi.org/10.32479/ijeep.10762